Analysis of financial and tax risks and countermeasures of administrative institutions - Yelong Jin* (International Scientific Technical and Economic Research, 2025)
Administrative institutions undertake a variety of administrative functions, with the nature of public welfare, which promote social and economic development, in public health, education, scientific research and other public professional services. With the further development of China’s market economy, administrative institutions are faced with complex and changeable internal and external environment. At this stage, there are still some problems in the management of financial and tax revenue in China’s administrative institutions, which affect the orderly development of financial and tax work. This paper analyzes the common problems of financial taxation of administrative institutions and puts forward its countermeasures, in order to provide reference for the development of the industry and further provide help for the stable and healthy development of administrative institutions.